2012
DOI: 10.1002/eji.201242483
|View full text |Cite
|
Sign up to set email alerts
|

CTL recognition of HIV‐1‐infected cells via cross‐recognition of multiple overlapping peptides from a single 11‐mer Pol sequence

Abstract: It is known that overlapping HIV‐1 peptides of different lengths can be presented by a given HLA class I molecule. However, the role of those peptides in CD8+ T cells recognition of HIV‐1‐infected cells remains unclear. Here we investigated the recognition of overlapping 8‐mer to 11‐mer peptides of Pol 155–165 by HLA‐B*54:01‐restricted CD8+ T cells. The analysis of ex vivo T cells using ELISPOT and tetramer binding assays showed that there were different patterns of CD8+ T‐cell responses to these peptides amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Previous studies indicated that HLA-B57-restricted KI8 and KF10 or HLA-B35-restricted VY8 and RY11 superimposed epitopes induce independent CTL responses (7,10), but that HLA-B54-restricted FV9 and FP10 superimposed epitopes elicit mainly cross-reactive CTLs in HIV-1-infected patients (8). Although the detailed mechanisms remain unclear, these studies suggest that different lengths or conformations of a peptide may determine the nature of the CTL response.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies indicated that HLA-B57-restricted KI8 and KF10 or HLA-B35-restricted VY8 and RY11 superimposed epitopes induce independent CTL responses (7,10), but that HLA-B54-restricted FV9 and FP10 superimposed epitopes elicit mainly cross-reactive CTLs in HIV-1-infected patients (8). Although the detailed mechanisms remain unclear, these studies suggest that different lengths or conformations of a peptide may determine the nature of the CTL response.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, two epitopes in which a shorter one is embedded within a longer one are defined as superimposed epitopes, and they have been shown to be presented by the same MHCI molecule (4)(5)(6). A number of studies have reported CTL responses against such superimposed peptides in the context of an HIV-1 infection (7)(8)(9)(10). For instance, these responses include CTLs specific for HLA-B57-restricted p24 Gag-derived peptides, for example, KI8 (residues 162-169, KAFSPEVI) and KF11 (residues 162-172, KAFSPEVIPMF), as well as for HLA-B*35:01-restricted Nef-derived peptides, for example, VY8 (residues 74-81, VPLRPMTY) and RY11 (residues 71-81, RPQVPLRPMTY).…”
Section: Ytotoxic Cd8mentioning
confidence: 99%
“…However, this may be an underestimate. The frequency may be higher if HIV-1-specific T cells are measured by tetramers, since the ELISpot assay is less sensitive than the tetramer-binding one (47). The frequency of HIV-1-specific T cells is much lower in ART patients than in treatmentnaïve ones (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…HLA-B*40:06-PolGA9 or -PolLA9 peptide tetrameric complexes (tetramers) and HLA-B*40:02-PolGI8, HLA-A*24:02-NefRF10 or -GagKW9, HLA-B*54:01-PolFP10, -PolFV9, or -PolFV11, HLA-A*11:01-NefQK10 complexes were generated as previously described ( 33 , 37 , 38 , 45 ). PBMCs or the bulk T cells were stained with phycoerythrin-conjugated epitope-specific tetramers at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%